Game based approach in learning Malay proverbs / Siti Nur Shafirah Mokhtar ... [et al.] - Mokhtar, Siti Nur Shafirah; Hasnan, Mazliana; Dahlan, Azlin; Abdullah, Zamlina (Faculty of Computer and Mathematical Sciences, 2021)
Proverbs are a basic component in Bahasa Melayu and are one of the important elements in completing Bahasa Melayu skills for primary school. Using proverbs effectively in writing contributes to good writing. However, from the preliminary study conducted at a primary school, the findings showed that students find it difficult to understand the Malay proverbs and its meaning. In addition, the learning environment is not interesting. Thus, this research has developed a game named Bijak Peribahasa Game to give users an enjoyable learning experience to learn the Malay proverbs. The game is developed using the Game Development Life Cycle Model (GDLC). The enjoyment level of the game is evaluated by using an adaptation of the EGameFlow Model including concentration, goal clarity, feedback, challenge, autonomy, immersion and knowledge improvement. Findings of enjoyment evaluation showed that the game receives 95% level of agreeability by the game users. Future work for this game includes developing on mobile platforms, providing high scores for players, improving by adding multi-player and enhancing the contents of the game.